THE ROLE OF TELEVISION TO INCREASE THE POLITICAL PARTICIPATION OF THE SOCIETY IN THE PRESIDENT’S ELECTION OF 2014 (Case in Desa Landungsari Malang) - Sumarsono Soemardjo (Puslitbang Literasi dan Profesi SDM Komunikasi dan Informatika, 2015)
The role of television is hoped to increase the participation of the society in politics, since it has the power to reach remote villages. This research is intended to perceive whether the material/information in connection with the General Election could be comprehended and arouse the political participation of the society during the President’s General Election in 2014. The qualitative research which was implemented by performing a survey in Landungsari Village, Dau sub-district, Malang Regency, East Java, with the sample of 101 respondents, was able to reach a finding: the General Election messages conveyed on television had reached the respondents. Nevertheless, in enhancing the participation of the society in politics during the President’s General Election in 2014, persistent interpersonal communication by the society’s information agent is still required. Key words: Television, General Election, the participation of the society in politics